Case Report: Expanding the Genetic and Phenotypic Spectrum of Autosomal Recessive Spastic Ataxia of Charlevoix-Saguenay - Habibzadeh, Parham; Tabatabaei, Zahra; Inaloo, Soroor; Nashatizadeh, Muhammad Mahdi; Synofzik, Matthis; Ostovan, Vahid Reza; Faghihi, Mohammad Ali (Frontiers in Genetics, 2020)
Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a rare neurodegenerative disorder caused by biallelic mutations in the SACS gene. Once thought to be limited to Charlevoix-Saguenay region of Quebec, recent evidence has indicated that this disorder is present worldwide.It is classically characterized by the triad of ataxia, pyramidal involvement, and axonal-demyelinating sensorimotor neuropathy. However, diverse clinical features have been reported associated with this disorder. In this report, we present the first Iranian family affected by ARSACS with unique clinical features (mirror movements, hypokinesia/bradykinesia, rigidity)harboring a novel deletion mutation in the SACS gene. Our findings expand the genetic and phenotypic spectrum of this disorder.